If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 2) + -3 = 2x + 1 Reorder the terms: 4(2 + x) + -3 = 2x + 1 (2 * 4 + x * 4) + -3 = 2x + 1 (8 + 4x) + -3 = 2x + 1 Reorder the terms: 8 + -3 + 4x = 2x + 1 Combine like terms: 8 + -3 = 5 5 + 4x = 2x + 1 Reorder the terms: 5 + 4x = 1 + 2x Solving 5 + 4x = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 5 + 4x + -2x = 1 + 2x + -2x Combine like terms: 4x + -2x = 2x 5 + 2x = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 5 + 2x = 1 + 0 5 + 2x = 1 Add '-5' to each side of the equation. 5 + -5 + 2x = 1 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 1 + -5 2x = 1 + -5 Combine like terms: 1 + -5 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| 5-3(4-2b)=4(b-3) | | 19-20b=18 | | 3x-(x+1)=41 | | 16n=5n | | 5x-12=4-6x | | -2(-3x)=8x+2x | | -37=3-8x | | 19x=49-10 | | 6x-4-3x=20 | | (3a+7)(2a-5)= | | 4x^2+47x+70=0 | | 10(x+.50)=3x+5+7x | | (-19)*y=1900 | | 36x=8x | | 4x+8x=12-10 | | x^3-5x^2+12=0 | | 5+-11n=24 | | (12)(-5)n=0 | | 42=-29(y+5) | | -7(y+4)-6y= | | X^2-7x=-144 | | 2x+x+4+2=3(x+2) | | 49=7f | | b+5=-2b-3 | | 7+2(x-6)=-3+2x(x-1) | | 2(y-4)=-3(y+2)-8 | | x-23=-100 | | 6x^2+3x-135=0 | | -3(-6-2z)=3z | | X^2+7x=-144 | | -24z+17=22 | | (x-4)p(x)=x^2+8x-48 |